How Collaborative Writing Influence Psychological Factor: An Investigation of Interaction Anxiousness among College English Students in China - Miao, Yiran; YANG, HE; Yu , Sihui (International Theory and Practice in Humanities and Social Sciences, 2025)
Among Chinese university students, social anxiety has emerged as a prevalent psychological issue. Psychology has conducted extensive research and made concerted efforts to alleviate social anxiety among college students. However, current investigations indicate that social anxiety remains widespread, affecting not only students’ academic and daily life on campus but also influencing their behavior and thought patterns in future professional and personal settings. This study aims to explore whether collaborative writing in foreign language classrooms can mitigate students’ social anxiety levels in daily life. Utilizing a qualitative research approach, semi-structured interview were conducted with 20 participating students. Findings indicate that collaborative writing pedagogy in foreign language classrooms not only effectively reduces students’ social anxiety but also positively influences their social thinking patterns.